Pengaruh Kematangan Emosi Dan Dukungan Sosial Teman Sebaya Terhadap Coping Pada Siswa Kelas Xii SMA Plus YPBH Bogor - Fadilah, Afiah Nur; Nurhadianti, RR Dini Diah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
This study aims to determine the influence of emotional maturnity and peer social supporton coping in students of class XII SMA PLUS YPHB Bogor.The population in this study was244 students of class XII.The sampling technique in this study was Conveniencesampling.Convenience is where the research sample is the easiest individual or organizationfor researchers to find.The measuring instruments used are the emotional maturity scale (16items α = 0.805) and the peer social support scale (25 items α = 0.947).The results showeda positive influence between Emotional Maturity to Coping by 0.186 and there was apositive influence between Peer Social Support to Coping of 0.236.Furthermore, the results of data analysis with Multiple Regression using IBM SPSS Statistic 22 obtained R square =0.271and p = 0.000 < 0.5.This shows that there is an Influence of Emotional Maturity andPeer Social Support on Coping in students of class XII SMA PLUS YPHB Bogor